Pengaruh Integritas dan Kualitas SDM terhadap Pengelolaan Keuangan Desa di Kabupaten Sidoarjo - Muhamad Khalid Abdillah; Galih Wahyu Pradana (Lembaga Pengembangan Kinerja Dosen, 2025)
Good financial management at the village level is crucial to support development and the welfare of the village community. However, many villages still face challenges in financial management, one of which is the low quality of human resources (HR) and the lack of integrity among village officials. This study aims to analyze and evaluate the influence of integrity on village financial management, as well as to analyze and evaluate the influence of human resource quality on village financial management, using 35 village governments in Sidoarjo Regency as the research location. This research was conducted by distributing questionnaires to 232 respondents, with the study population being the entire population of Sidoarjo Regency, totaling 1.977 million people, to examine the independent variables (integrity and HR quality) in relation to the dependent variable (village financial management). The method used in this research is Structural Equation Modeling (SEM), with data processing conducted using Smart-PLS 4 software. The results of the study show that the integrity of village officials has a positive influence on village financial management at a rate of 0.444, meaning that the higher the integrity of village officials, the better the financial management of the village. Additionally, HR quality was also found to have a significant impact on village financial management at a rate of 0.420. This research contributes to improving village financial management by emphasizing the importance of integrity and the quality of human resources in village governance.